2011
DOI: 10.1186/1741-7015-9-69
|View full text |Cite
|
Sign up to set email alerts
|

α-Mangostin extracted from the pericarp of the mangosteen (Garcinia mangostanaLinn) reduces tumor growth and lymph node metastasis in an immunocompetent xenograft model of metastatic mammary cancer carrying a p53 mutation

Abstract: BackgroundThe mangosteen fruit has a long history of medicinal use in Chinese and Ayurvedic medicine. Recently, the compound α-mangostin, which is isolated from the pericarp of the fruit, was shown to induce cell death in various types of cancer cells in in vitro studies. This led us to investigate the antitumor growth and antimetastatic activities of α-mangostin in an immunocompetent xenograft model of mouse metastatic mammary cancer having a p53 mutation that induces a metastatic spectrum similar to that see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
88
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(101 citation statements)
references
References 46 publications
6
88
0
3
Order By: Relevance
“…The chemical structures of 8 major xanthones contained in pericarps are shown in Figure 1. They have been attracting much attention because of their pharmacological activity, such as anti-allergy [6], anti-bacterial [7,8], anti-tumoral [9,10], anti-inflammatory [11], anti-oxidant [12][13][14] and anti-hypertensive properties [15]. Also, they were observed to induce apoptosis by targeting mitochondria of a decreased membrane potential, leading to the activation of the intrinsic apoptotic signal transduction [16].…”
mentioning
confidence: 99%
“…The chemical structures of 8 major xanthones contained in pericarps are shown in Figure 1. They have been attracting much attention because of their pharmacological activity, such as anti-allergy [6], anti-bacterial [7,8], anti-tumoral [9,10], anti-inflammatory [11], anti-oxidant [12][13][14] and anti-hypertensive properties [15]. Also, they were observed to induce apoptosis by targeting mitochondria of a decreased membrane potential, leading to the activation of the intrinsic apoptotic signal transduction [16].…”
mentioning
confidence: 99%
“…It is well known that alpha-mangostin exhibited a broad spectrum of biological effects including anti-oxidant [8], anti-inflammatory [9], anti-allergic [10], analgesic [11], neuro-protective [12], anti-mycobacterial [1], antifungal [13], anti-bacterial [14] and anti-proliferative [15,16] activities. In addition, recent studies have indicated that alpha-mangostin had anti-metastatic effect against various cancer cell lines [17][18][19]. Nevertheless, the results of pharmacokinetic study of pure alphamangostin revealed its low oral bioavailability attributed to the first pass metabolism beside its non-selective distribution into the rat tissue [20].…”
Section: Introductionmentioning
confidence: 97%
“…The chromatographic separation was performed at ambient temperature using Hypersil  BDS C 18 column (4.6×100 mm, 3 μm) with C 18 …”
Section: Instrumentation and Chromatographic Conditionmentioning
confidence: 99%
“…Phosphorylated and total ERK, JNK, and Akt were downregulated in α-MG-treated SW1353 cells, but there were no changes in p38 MAPK [88]. In both mammary carcinoma cells in culture and tissues in vivo, α-MG significantly decreased the levels of phospho-Akt-Thr308 [27]. In addition, there is substantial evidence that α-MG restrained the process of invasion and migration in cancer cells by acting on the MAPK or Akt pathway.…”
Section: Inhibition Of Survival Pathwaysmentioning
confidence: 99%
“…Importantly, besides the inhibitory effects on the growth of primary tumors, α-MG has also shown significant antimetastatic effects in animal models. Shibata et al [27] successfully developed a metastatic cancer model by implanting murine mammary adenocarcinoma BJMC3879luc2 cells into syngeneic BALB/c mice, which induces a metastatic spectrum similar to that seen in human breast cancer. Using this model, they confirmed that α-MG significantly attenuated the growth of tumors and the multiplicity of lymph node metastasis.…”
Section: Antitumor Activity Of Mangostin In Animal Modelsmentioning
confidence: 99%